A systematic study and effect of PLA/Al2O3 nanoscaffolds as dental resins: mechanochemical properties - Mehdi Ranjbar; Gholamreza Dehghan Noudeh; Maryam-Alsadat Hashemipour; Iman Mohamadzadeh (Artificial Cells, Nanomedicine, and Biotechnology)
One of the major and important challenges in dental composite resin and restoration is the mechanical performance and property of materials. Nanotechnology can produce nanoscale materials that are used in dentistry to help stabilize and strengthen the dentistry. In this work, we study the synthesis and characterization of PLA/Al2O3 nanoscaffold in different conditions such as concentration, temperature, pH, microwave power and irradiation time. PLA/Al2O3 nanoscaffolds were prepared by a micelle-assisted hydrothermal method. Durability, stability and biodegradable nature of nanopolymers have created the much-applied potential for using this structures in many fields such as dental resin composites. Products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transition electron microscopy (TEM), Fourier transformed infrared spectrum (FT-IR), Dynamic light scattering (DLS) and atomic force microscopy (AFM). The synthesis factors were designed by Taguchi technique to control the process systematically. It was found that the intermolecular crosslinks between PLA and Al2O3 nanoparticles cause significant improves in the mechanical properties of PLA/Al2O3 nanoscaffold as dental nanocomposites. The flexural strength (88.0 MPa), modulus (7.5 GPa) and compressive strength (157.2 MPa) were calculated for PLA/Al2O3 nanoscaffolds loaded in Heliomolar Flow composite resins at 80 ppm (wt) concentration.